SALES OPTIMIZATION ANALYSIS USING SIMPLEX METHOD IN SMALL MEDIUM BUSINESS - Rumetna, Matheus Supriyanto; Lina, Tirsa Nina; Tindage, Jalminj (Journal of Computer Science and Technology (JCS-TECH), 2022)
Competition in the business world is now getting faster, coupled with the Covid-19 pandemic, making many small-scale businesses suffer losses and close their businesses. One of them is the business owned by Mr. Wartono which also experienced the same thing plus the problem related to determining the optimum sales production amount, so as to generate maximum sales profit. This problem can be solved using the simplex method which is one part of the Linear Program and utilizes information technology, namely POM-QM software for Windows V5. The purpose of using OT, especially the simplex method, is to assist in decision making. The results of this study provide optimal profits from the amount of sales production.